Identification of Small‐Molecule PHD2 Zinc Finger Inhibitors that Activate Hypoxia Inducible Factor. (11th November 2016) - Arsenault, Patrick R.; Song, Daisheng; Bergkamp, Marian; Ravaschiere, Andrew M.; Navalsky, Bradleigh E.; Lieberman, Paul M.; Lee, Frank S.
Abstract: The prolyl hydroxylase domain (PHD) protein:hypoxia inducible factor (HIF) pathway is the main pathway by which changes in oxygen concentration are transduced to changes in gene expression. In mammals, there are three PHD paralogues, and PHD2 has emerged as a particularly critical one for regulating HIF target genes such as erythropoietin ( EPO ), which controls red cell mass and hematocrit. PHD2 is distinctive among the three PHDs in that it contains an N‐terminal MYND‐type zinc finger. We have proposed that this zinc finger binds a Pro‐Xaa‐Leu‐Glu (PXLE) motif found in proteins of the HSP90 pathway to facilitate HIF‐α hydroxylation. Targeting this motif could provide a means of specifically inhibiting this PHD isoform. Here, we screened a library of chemical compounds for their capacity to inhibit the zinc finger of PHD2. We identified compounds that, in vitro, can inhibit PHD2 binding to a PXLE‐containing peptide and induce activation of HIF. Injection of one of these compounds into mice induces an increase in hematocrit. This study offers proof of principle that inhibition of the zinc finger of PHD2 can provide a means of selectively targeting PHD2 to activate the HIF pathway. Abstract : Give me a HIFive ! The zinc finger of prolyl hydroxylase domain 2 (PHD2) plays a critical role in the oxygen‐dependent control of hypoxia inducible factors (HIFs). Using a novel high‐throughput screen and cell and animal models, we identified small‐molecule inhibitors of this domain and showed that one led to increased red cell mass, a hallmark of HIF activation.